Salinomycin, as an autophagy modulator-- a new avenue to anticancer: a review - Jiang, Jiang (J Exp Clin Cancer Res, 2018)
Since Salinomycin (Sal) emerged its ability to target breast cancer stem cells in 2009, numerous experiments have been carried out to test Sal’s anticancer effects. What deserve to be mentioned is that Sal can efficiently induce proliferation inhibition, cell death and metastasis suppression against human cancers from different origins both in vivo and in vitro without causing serious side effects as the conventional chemotherapeutical drugs on the body. There may be novel cell death pathways involving the anticancer effects of Sal except the conventional pathways, such as autophagic pathway. This review is focused on how autophagy involves the effects of Sal, trying to describe clearly and systematically why autophagy plays a vital role in predominant anticancer effects of Sal, including its distinctive characteristic. Based on recent advances, we present evidence that a dual role of Sal involving in autophagy may account for its unique anticancer effects - the preference for cancer cells. Further researches are required to confirm the authenticity of this suppose in order to develop an ideal anticancer drug.